The Social Representation of Ulama in Banjar Culture: An Indigenous Psychology Study of the Figure of "Guru Kapuh" - Hidayat, Taufik; Hairina, Yulia; Imadduddin, I (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study investigates the social representation of KH. Muhammad Ridwan Baseri, popularly known as Guru Kapuh, a respected ulama within Banjar society in South Kalimantan, Indonesia. His leadership extends beyond the role of a religious teacher, embodying dimensions of civic engagement, cultural symbolism, and emotional support. Framed within the lens of Indigenous Psychology, the study examines how the Banjar community perceives, internalizes, and reproduces his image through everyday practices, shared narratives, and cultural values. Religious leaders in Indonesia, particularly in pesantren-based contexts, have historically functioned as moral anchors and agents of cultural transmission. Yet, there is limited research on how such figures are socially represented in the lived experience of communities. This study seeks to fill that gap by analyzing Guru Kapuh's multifaceted role, highlighting how he integrates Sufi teachings, civic responsibility, and local wisdom into his leadership.The research employed a qualitative descriptive design to capture the depth of participants' lived experiences. Data were collected through semi-structured interviews with students, local residents, religious scholars, and government officials, complemented by documentation and media analysis. Purposive sampling was used to identify participants who had sustained interaction with Guru Kapuh in religious, educational, or civic contexts. Thematic analysis was applied to transcribed data, enabling the identification of recurring cultural patterns and shared representations. This methodological approach, grounded in Indigenous Psychology, ensured that interpretations reflected the cultural context and symbolic worldviews of the Banjar people rather than imposing external theoretical constructs.Thematic analysis revealed five interconnected domains of representation. First, spiritual leadership was identified as the foundation of Guru Kapuh's influence. His teachings emphasized Sufi ethics-such as humility, sincerity (ikhlas), and inner purification (tazkiyah al-nafs)-while his personal piety reinforced his credibility as a moral exemplar. Followers viewed him as a living model of virtue, whose embodiment of Islamic values inspired introspection and ethical conduct. Second, civic engagement highlighted his partnership with local government officials, exemplifying the Banjar cultural principle of ulama–umara synergy. As chairman of the local Indonesian Ulema Council (MUI), he provided religious legitimacy and moral direction in governance, particularly during crises such as natural disasters or social unrest. His balanced guidance reinforced institutional legitimacy and promoted communal stability. Third, educational legacy underscored his contributions to Islamic education through the founding of pesantren (Islamic boarding schools) and the organization of majelis taklim (study circles). These institutions were valued not only for academic instruction but also for nurturing character, moral integrity, and intergenerational transmission of religious values. His pedagogy emphasized sincerity and understanding, encouraging reflective rather than rote religiosity. Fourth, as a cultural symbol of harmony, Guru Kapuh embodied the integration of religion and local tradition. He often drew upon Banjar proverbs to communicate Islamic values in accessible terms, reinforcing communal ideals of tolerance, cooperation, and moral responsibility. His presence as a mediator between community and government affirmed his symbolic role as a custodian of cultural wisdom. Fifth, personal guidance and counseling revealed the intimate aspect of his leadership. Community members frequently sought his counsel during times of emotional distress, family conflict, or spiritual doubt. His non-directive approach, grounded in compassion (rahmah) and empathetic listening, provided emotional reassurance and psychological relief, making him a trusted confidant for individuals navigating personal crises.The findings suggest that Guru Kapuh represents a holistic model of religious leadership that transcends formal authority by integrating spirituality, civic responsibility, education, cultural wisdom, and personal care. His authority derives less from institutional position and more from relational ethics, moral consistency, and affective presence. This reflects broader Indigenous Psychology principles, where leadership is legitimized through lived practice, cultural resonance, and community trust. By embedding Islamic teachings within local cultural idioms, Guru Kapuh exemplified a contextualized Islam that resonated deeply with daily life and social identity. Methodologically, the study demonstrates the value of Indigenous Psychology in uncovering localized moral worlds and collective identities. It challenges universalist models of leadership by foregrounding relational, affective, and cultural dimensions often overlooked in mainstream psychology. The implications extend to community mental health, education, and governance, where collaboration with local religious figures may strengthen social cohesion and resilience. In conclusion, KH. Muhammad Ridwan Baseri (Guru Kapuh) stands as a testament to the enduring power of ethical leadership rooted in local culture and lived spirituality. His legacy provides a model for rethinking leadership-not as hierarchy or dominance, but as service, sincerity, and spiritual embodiment that uplifts individuals and strengthens communal harmony. As societies face ongoing moral fragmentation and global challenges, figures like Guru Kapuh highlight the potential of indigenous frameworks for cultivating social harmony and resilience in Muslim-majority contexts.